2020
DOI: 10.48550/arxiv.2007.01665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pulsating strings in $Schr_5 \times T^{1,1}$ background

A. Golubtsova,
H. Dimov,
I. Iliev
et al.

Abstract: The quest for extension of holographic correspondence to non-relativistic sectors naturally includes Schrödinger backgrounds and their field theory duals. In this paper we study the holography by probing the correspondence with pulsating strings. The case we consider is pulsating strings in five-dimensional Schrödinger space times five-torus T 1,1 , which has as field theory dual a dipole CFT. First we find particular pulsating string solutions and then semi-classically quantize the theory. We obtain the wave … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…For these reasons, and the fact that currently very little is known for dipole theories, we are motivated to investigate the properties of such holographic models on both sides of the correspondence. Further studies of non-relativistic holography in Shrödinger spacetime can be found in [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, and the fact that currently very little is known for dipole theories, we are motivated to investigate the properties of such holographic models on both sides of the correspondence. Further studies of non-relativistic holography in Shrödinger spacetime can be found in [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned results are in complete agreement with the form of the correlator dictated by non-relativistic conformal invariance and provide us with the leading term of the correlators in the large λ expansion. Finally, pulsating strings solutions in the Schrödinger background were recently derived in [24,25] while the holographic Fisher information metric in Schrödinger spacetime was studied in [26].…”
Section: Introductionmentioning
confidence: 99%